Vagococcus salmoninarum I—A chronic coldwater streptococcosis in broodstock brook trout (Salvelinus fontinalis) in Wisconsin, USA. Issue 3 (6th February 2020) - Standish, Isaac; Erickson, Sara; Leis, Eric; Baumgartner, Wes; Loch, Thomas; Knupp, Christopher; McCann, Rebekah; Puzach, Corey; Katona, Ryan; Lark, Ellen; Bailey, Jennifer; Buening, Jorge; et al.
Abstract: In 2018, Vagococcus salmoninarum was isolated from two lots of broodstock "coaster" brook trout ( Salvelinus fontinalis ) containing 1, 500 fish at the Iron River National Fish Hatchery, at which time it was identified as the causative agent of a chronic coldwater streptococcosis epizootic. Clinical signs included exophthalmia, lethargy, erratic swimming and loss of equilibrium. Female fish experienced disproportionately higher morbidity and mortality than male co‐inhabitants, and routinely retained eggs following spawning. The most consistent gross clinical sign was heart pallor and turbid pericardial effusion. An attempted treatment using florfenicol was ineffective at halting the epizootic, which spanned more than a year and resulted in >50% mortality before remaining fish were culled. As there is no previous documentation of V. salmoninarum at this hatchery or in this species, it is still unclear what circumstances led to this epizootic. The inability to treat this chronic disease led to the loss of valuable broodstock, hampering ongoing fishery conservation efforts in the Great Lakes Basin.